Gyro-TWT using a metal PBG waveguide as Its RF circuit - Part II: PIC simulation and parametric analysis - Thottappan M.; Singh P.; Jain P.K. (My University, 2025)
In this paper, 3-D electromagnetic particle-in-cell (PIC) simulation of gyro-TWT amplifier using a metal photonic bandgap (PBG) waveguide as its RF interaction circuit is presented. A commercial finite integration-based PIC simulation code CST Particle Studio has been used to study the beam-wave interaction mechanism. The mode selectivity of a PBG waveguide has been investigated in the absence of an electron beam, so as to obtain the single-mode operation in a gyro-TWT. The simulated PBG gyro-TWT produced a stable RF output power of ∼ 90 kW at 35 GHz for a 72-keV, 10-A annular electron beam with a velocity ratio of 1.05. The instantaneous bandwidth has been obtained as ∼ 14 % with respect to the operating frequency. Furthermore, the performance of the simulated PBG gyro-TWT has also been investigated through the parametric variation of the velocity spread, beam voltage, beam current, axial magnetic field, beam pitch factor, and the RF input power to validate the conceptual design of the device. © 1963-2012 IEEE.